Penerapan Model Discovery Learning Guna Meningkatkan Keaktifan Belajar Siswa dalam Mata Pelajaran Kimia pada Kelas X TSM A SMK Muhamadiyah 1 Palu - Hajemia, Hajemia (Jurnal Kreatif Online, 2020)
This study aims to increase the learning activeness of 10th grade students of TSM A SMK Muhammadiyah 1 Palu by applying the discovery learning model. This research was a classroom action research (PTK) which was conducted in 3 cycles. Each cycle consists of three steps according to Kemmis & McTaggart, which are planning, acting and observing, and reflecting. The subjects of this study were 30 students of grade 10th of SMK Muhammadiyah 1 Palu who were in odd semester 2019/2020 academic year. The data in this study were obtained through the student learning activeness observation sheet. The data were analyzed using the quantitative data analysis technique of learning activity. Learning activity was categorized successful if the percentage of students who passed the passing grade was at least 76%. The result of this research indicated that the discovery learning model can increase the learning activeness of class 10th graders of TSM A students of SMK Muhammadiyah 1 Palu. It was revealed by the increase in the percentage of student learning activeness in the first cycle by 31.42% with the criteria of "very poor". In the implementation of cycle II, the percentage of student learning activeness was 67.61% with the criteria "sufficient". While the implementation of the third cycle, the percentage of student learning activeness was 79.04% with "good" criteria. This research was stopped in the third cycle because the results have achieved the minimum success standard category.Â